RAGAM TINJAUAN ASPEK PENGEMBANGAN PROFESIONAL KEPEMIMPINAN PENDIDIKAN - Eka Abdul Hamid; Asep Surya Atmaja; Ishak Abdulhak; Achmad Mudrikah (Almarhalah | Jurnal Pendidikan Islam, 2021)
AbstractThe reality in the field is that there are still many principals who do not carry out their duties and functions as educational leaders because in the process of appointment there is no transfer, the low mentality of the principal is marked by a lack of motivation and enthusiasm and lack of discipline in carrying out tasks and often arrives late and many factors Another obstacle to improving the quality of education implies low work productivity of school principals which also has implications for quality (inputs, processes, and outputs), this is inversely proportional to example. Therefore, to find out how to improve the quality of the principal's competence, more in-depth research is needed regarding the Professional Development of Educational Leadership. From this phenomenon, several research problems were formulated to find answers to the nature of the professional development of educational leadership at SMKN 1 Buahdua, how is the basis of religion, philosophy, psychology, and sociology for the development of professional leadership in education at SMKN 1 Buahdua. The methodology used in writing this paper is descriptive qualitative method with Library Research and field research approaches. Field research was carried out using interviews with the leadership and other parties related to visits to several locations in the school environment. The results of the study, the Religious Foundations of Professional Development of Educational Leadership at SMKN 1 Buahdua lead to Q.S Ali-Imron: 159 about deliberation and monotheism of the principal and noble character; wise and prudent; democratic; honest; sportsmanship; sincere in carrying out their duties with indicators always praying for their students. In terms of self-potential, Q.S Al-Isro: 70 emphasizes increasing self-potential at SMKN 1 Buahdua, especially the principal. The foundation of the Philosophy of Professional Development of Educational Leadership at SMKN 1 Buahdua leads to a Progressivism Philosophy which is always the principal continuously updates himself with various self-development efforts by continuing to hone experience so that the role of the principal at SMKN 1 Buahdua increases. The foundation of Psychology of Professional Development of Educational Leadership at SMKN 1 Buahdua leads to Developmental Psychology where the Principal as the leader of Education there continues to develop himself with various efforts, such as attending seminars. The Sociological Foundation of Professional Development of Educational Leadership at SMKN 1 Buahdua leads to an intergalactic understanding because indeed to develop professional education leaders, the principal always makes efforts to improve professionalism in leading schools by participating in various types of training in various seminar activities.Keywords: Professional Development; Educational Leadership; Religion; Philosophy; Psychology; Sociology.